Understanding and reducing photothermal forces for the fabrication of Au nanoparticle dimers by optical printing - Gargiulo, Julian (2017)
Optical printing holds great potential to enable the use of the vast variety of colloidal nanoparticles (NPs) in nano- and microdevices and circuits. By means of optical forces, it enables the direct assembly of NPs, one by one, onto specific positions of solid surfaces with great flexibility of pattern design and no need of previous surface patterning. However, for unclear causes it was not possible to print identical NPs closer to each other than 300 nm. Here, we show that the repulsion restricting the optical printing of close by NPs arises from light absorption by the printed NPs and subsequent local heating. By optimizing heat dissipation, it is possible to reduce the minimum separation between NPs. Using a reduced graphene oxide layer on a sapphire substrate, we demonstrate for the first time the optical printing of Au-Au NP dimers. Modeling the experiments considering optical, thermophoretic, and thermo-osmotic forces we obtain a detailed understanding and a clear pathway for the optical printing fabrication of complex nano structures and circuits based on connected colloidal NPs.